Two-Step Surgical Strategy for Parathyroid Carcinoma: A Single-Center Experience - Filippo Longo; Antonio Sarubbi; Claudia Palladino; Andrea Palermo; Anda Mihaela Naciu; Anna Crescenzi; Chiara Taffon; Gaia Tabacco; Luca Frasca; Pierfilippo Crucitti (Medicina)
Parathyroid carcinoma (PC) is a rare endocrine malignancy that poses significant diagnostic challenges due to its resemblance to benign conditions. This case series describes the clinical presentation, diagnosis, management, and short-term outcomes of four male patients (aged 54, 65, 73, and 74 years) with primary hyperparathyroidism and hypercalcemia. The preoperative diagnosis of PC remains challenging; suspicion should arise in cases of severe hypercalcemia, elevated parathyroid hormone levels, and the presence of a mass on imaging or during surgery. All patients underwent an initial localized parathyroidectomy, with PC confirmed postoperatively. Subsequently, they received ipsilateral hemithyroidectomy and prophylactic central lymph node dissection. Over a two-year follow-up period, all patients maintained normocalcemia without evidence of disease recurrence or metastasis. In conclusion, whether to perform a complete en bloc resection or a two-step surgical strategy remains a difficult decision in PC patients with intricate preoperative evaluations.